FOSTERING YOUNG LEARNERS’ VOCABULARY MASTERY BY USING PEER-ASSISTED LEARNING STRATEGY IN PRIMARY EFL CLASSROOMS - Ilham Saputra; Ari Purnawan; Maria Paulina Rohi (ENGLISH EDUCATION STUDY PROGRAM, FACULTY OF TEACHER TRAINING AND EDUCATION, UNIVERSITAS SRIWIJAYA, 2025)
Vocabulary is a foundational component of language learning, especially for young learners, as it directly impacts their mastery of language skills and overall academic success. This study investigates the effectiveness of the Class Wide Peer Tutoring (CWPT) model, a Peer-Assisted Learning Strategies (PALS), in enhancing fifth graders’ vocabulary mastery in Jogjakarta Primary School A pre-experimental one-group pre-test-post-test design was employed with a sample of 29 students. Students participated in three peer-assisted learning sessions focusing on the CWPT model, where they alternated roles between tutor and learner, engaging in vocabulary-related activities. The results of the pre-test and post-test were analysed using descriptive statistics and a paired sample t-test to determine the impact of Peer Assisted Learning Strategies (PALS) on students' vocabulary development. The findings revealed a statistically significant improvement, t(28) = –13.54, p < .001, with the mean post-test score (93.28) substantially higher than the pretest mean (48.79). The intervention enhances overall vocabulary knowledge and reduces the variability in students’ performance, indicating that lower-performing students benefited considerably from Peer Assisted Learning. This study provides practical insights into how peer-assisted learning can foster engagement, provide individualized support, and address diverse learning.